2020
DOI: 10.1111/1759-7714.13624
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA HCG11 sponging miR‐522‐3p inhibits the tumorigenesis of non‐small cell lung cancer by upregulating SOCS5

Abstract: Background: Numerous studies have shown that long non-coding RNA (lncRNA) is involved in various human diseases including non-small cell lung cancer (NSCLC). The aim of this study was to explore the potential role of lncRNA HCG11 in the pathogenesis of NSCLC. Methods: The mRNA expression of HCG11, miR-522-3p and SOCS5 was detected by RT-qPCR. The regulatory mechanism of lncRNA HCG11 was investigated by CCK-8, transwell and dual luciferase reporter assays. Results: Downregulation of lncRNA HCG11 and upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Multiple studies have found associations between SOCS5 expression levels and pathological conditions such as cancer. SOCS5 is upregulated in esophageal squamous cell carcinoma [ 22 ], liver cancer [ 23 ], non-small cell lung cancer [ 24 ], and prostate cancer [ 25 ]; hence, it is associated with specific biological characteristics of tumors. Moreover, SOCS5 partially reverses the inhibitory effect of miR-518c-3p on the invasion and migration of glioma cells [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have found associations between SOCS5 expression levels and pathological conditions such as cancer. SOCS5 is upregulated in esophageal squamous cell carcinoma [ 22 ], liver cancer [ 23 ], non-small cell lung cancer [ 24 ], and prostate cancer [ 25 ]; hence, it is associated with specific biological characteristics of tumors. Moreover, SOCS5 partially reverses the inhibitory effect of miR-518c-3p on the invasion and migration of glioma cells [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we also identified suppressor cytokine signaling-5 (SOCS5) was a negatively regulatory target of miR-522-3p using bioinformatics prediction and dual-luciferase assay. SOCS5 was also commonly found to be tumor-suppressed and significantly reduced in tumors, such as non-small cell lung cancer, pancreatic cancer and also liver cancer [ 43–45 ]. It was found that SOCS5 inhibition induced autophagy to impair metastasis in HCC cells via the PI3K/Akt/mTOR pathway [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOCS5 expression is regulated by several miRNAs. miR-522-3p was found to directly target SOCS5 to promote lung cancer cell viability, migration and invasion (Fan et al, 2020). A recent study showed that SOCS5 was a direct target of miR-675-3p, which activated PI3K signaling to maintain pancreatic cancer cell stemness (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%